The mentalist. The complete fifth season [videorecording (DVD)]. - Baker, Simon, 1969-; Baker, Simon, 1969-; Tunney, Robin; Yeoman, Owain, 1978-; Kang, Tim, 1973- (Warner Bros. Entertainment Inc., 2013)
Patrick Jane returns for Season Five of The Mentalist. Starring Emmy and Golden Globe nominee Simon Baker as the California Bureau of Investigation consultant and former faux-psychic obsessed with finding Red John, the serial killer who murdered his family.